2011
DOI: 10.5688/ajpe75468
|View full text |Cite
|
Sign up to set email alerts
|

Active-Learning Processes Used in US Pharmacy Education

Abstract: Objective. To document the type and extent of active-learning techniques used in US colleges and schools of pharmacy as well as factors associated with use of these techniques. Methods. A survey instrument was developed to assess whether and to what extent active learning was used by faculty members of US colleges and schools of pharmacy. This survey instrument was distributed via the American Association of Colleges of Pharmacy (AACP) mailing list. Results. Ninety-five percent (114) of all US colleges and sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
107
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 40 publications
1
107
0
1
Order By: Relevance
“…[10][11][12] In the pharmacy academy, active-learning strategies are recognized as important to achieving educational outcomes and, therefore, widely adopted in professional programs. [13][14][15] However, the use of active-learning strategies is not uniformly distributed. Faculty members in the biomedical and pharmaceutical sciences are 3 times less likely than faculty members in the clinical and social and administrative sciences to use these techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] In the pharmacy academy, active-learning strategies are recognized as important to achieving educational outcomes and, therefore, widely adopted in professional programs. [13][14][15] However, the use of active-learning strategies is not uniformly distributed. Faculty members in the biomedical and pharmaceutical sciences are 3 times less likely than faculty members in the clinical and social and administrative sciences to use these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Faculty members in the biomedical and pharmaceutical sciences are 3 times less likely than faculty members in the clinical and social and administrative sciences to use these techniques. 15 Process-oriented guided inquiry learning (POGIL) is a teaching strategy that was initially developed in college chemistry and biology courses and is used successfully to engage students in the classroom and to promote learning. [16][17][18][19][20] The POGIL strategy begins with introducing students to a model, diagram, problem, or set of data and then requires them to work as a team to answer a series of questions leading to development of a concept or principle (guided inquiry).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ARS is one of the most commonly used active learning strategies in US Colleges and Schools of Pharmacy [4]. Our experiment has shown that ARSs can be used to practice critical-thinking skills [45] since the MCQs included the determination of pros and cons of different concepts of human anatomy.…”
Section: Discussionmentioning
confidence: 86%
“…A recent study reported that about 87% of all colleges and schools of pharmacy in the United States (US) use active learning techniques [4]. One of the most beneficial means of active learning is collaborative learning, which can be achieved by putting students in small groups to work on a topic [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation